Knowledge and Awareness of Xerostomia Among Dental Practitioners in Tripoli, Libya - Aisha Shanan; Ebtesam Aldieb (AlQalam Journal of Medical and Applied Sciences, 2025)
Xerostomia, or dry mouth, is a common condition associated with reduced salivary flow. It often results from systemic diseases, some medications, radiation therapy, psychological factors, and aging. It significantly impacts oral health and patients’ quality of life, increasing the risk of dental caries and oral infections. Dental practitioners play a crucial role in its early diagnosis and management; however, their knowledge and awareness may differ widely. This study aimed to assess the knowledge and awareness of xerostomia among dental practitioners in Tripoli, Libya. A cross-sectional study was conducted among dental practitioners working in private clinics and public centers across Tripoli, Libya. Data were collected using a structured, self-administered questionnaire addressing demographics, knowledge of xerostomia etiology, and clinical management strategies. Statistical analysis was performed to evaluate associations between demographic variables and knowledge levels. A study of 139 dental practitioners found that 66.2% were female and 33.8% were male, with an average age of 38.04 ± 7.05 years. Most had a Bachelor of Dental Surgery (BDS) degree (64.0%) and postgraduate degrees, including Master of Dental Surgery (MDS) (22.3%) and PhD (13.7%). Nearly half of the dentists (49.6%) had over 10 years of clinical experience. Most of the participants identified xerostomia as "dryness of the mouth," with 87.8% of participants recognizing common symptoms of xerostomia. However, only 63.3% correctly identified key clinical signs. Most participants had high awareness of general causes of xerostomia, including Sjögren's syndrome. Regarding medication-induced xerostomia,74.8% of the participants identified drug classes such as antihistamines, antihypertensives, and antipsychotics as causes of xerostomia. Most respondents were familiar with general management strategies, but awareness of adjuvant therapies was low. The study highlights a moderate level of knowledge and awareness regarding xerostomia among dental practitioners in Tripoli. Continuing education programs focusing on the diagnosis and management of xerostomia are recommended to enhance patient care and improve clinical outcomes.